Extracting net current from an upstream neutral mode in the fractional quantum Hall regime - Gurman, I.; Sabo, R.; Heiblum, M.; Umansky, V.; Mahalu, D. (Nature communications, 2012)
Upstream neutral modes, counter propagating to charge modes and carrying energy without net charge, had been predicted to exist in some of the fractional quantum Hall states and were recently observed via noise measurements. Understanding such modes will assist in identifying the wavefunction of these states, as well as shedding light on the role of Coulomb interactions within edge modes. Here, operating mainly in the ν =2/3 state, we place a quantum dot a few micrometres upstream of an ohmic contact, which serves as a ‘neutral modes source’. We show that the neutral modes heat the input of the dot, causing a net thermo-electric current to flow through it. Heating of the electrons leads to a decay of the neutral mode, manifested in the vanishing of the thermo-electric current at T >110 mK. This set-up provides a straightforward method to investigate upstream neutral modes without turning to the more cumbersome noise measurements. One of the many exotic characteristics of systems that exhibit the fractional quantum Hall effect is the presence of chiral edge modes that carry energy but no net charge. Gurman et al. demonstrate the use of quantum dots to transform this energy into a measurable current, enabling them to better probe these modes.